Gene Expression Analysis of Somatic Embryogenesis in Oil Palm - Nuryanti Syariyanto; Utut Widyastuti; Nurita Toruan Mathius (International Journal of Oil Palm, 2018)
Multiplication of oil palm through somatic embryogenesis is hampered by low callogenesis and embryogenesis rates. Molecular marker based on RNA (transcriptomes analysis) is considered as one of the most e?ective techniques for detection and di?erentiation of embryogenic and non-embryogenic callus. A previous research using microarray technique had shown some potential candidate genes related to oil palm somatic embryogenesis, such as: IAA-amino acid hydrolase ILR1-like1 (ilr1), late embryogenesis abundant (lea2), 26S proteasome non-ATPase regulatory subunit 13 homolog B (26sp), and alpha trehalose phosphate synthase [UDP-forming] 6-like (tps6). The objective of this study was to analyze the transcription level of ilr1, lea2, 26sp, and tps6 using quantitative reverse transcription PCR (RT-qPCR). Non-embryogenic nodular callus and somatic embryo (coleoptile stage) of Elaeis guineensis var. Tenera (Deli Dura x AVROS Pisifera) leaf explants were collected from three palms for RNA extraction. The frst strand cDNA was synthesized from RNA and used for gene expression analysis. The expressions of four embryogenesis-related genes were analyzed using Relative Quantifcation Standart Curve method. RQ value was analyzed with One-way ANOVA and Dunnett’s test using Statistical Product and Service Solution (SPSS) 20.0 for windows. In RT-qPCR analysis, non-embryogenic nodular callus was used as calibrator sample and 40S ribosomal protein S27-2 (40s) was used as reference gene. The result shows that ilr1 and lea2 genes were signifcantly transcribed higher on coleoptile stage of the somatic embryo compared to callus, in other hand 26sp, and tps6 shows no expression di?erence on both samples.ilr1 genes gave the highest expression in somatic embryo compared to callus in most tested palms. Thus, it indicated that ilr1 may potentially involve in oil palm somatic embryogenesis and can be used as a candidate to develop the marker for embryogenesis in oil palm.